Comparison of MRI and colonoscopy in determining tumor height in rectal cancer. Issue 1 (February 2018) - Jacobs, Lotte; Meek, David B; van Heukelom, Joost; Bollen, Thomas L; Siersema, Peter D; Smits, Anke B; Tromp, Ellen; Los, Maartje; Weusten, Bas LAM; van Lelyveld, Niels
Background and aim: Endoscopy and magnetic resonance imaging (MRI) are used routinely in the diagnostic and preoperative work-up of rectal cancer. We aimed to compare colonoscopy and MRI in determining rectal tumor height. Methods: Between 2002 and 2012, all patients with rectal cancer with available MRIs and endoscopy reports were included. All MRIs were reassessed for tumor height by two abdominal radiologists. To obtain insight in techniques used for endoscopic determination of tumor height, a survey among regional endoscopists was conducted. Results: A total of 211 patients with rectal cancer were included. Tumor height was significantly lower when assessed by MRI than by endoscopy with a mean difference of 2.5 cm (95% CI: 2.1–2.8). Although the agreement between tumor height as measured by MRI and endoscopy was good (intraclass correlation coefficient (ICC) 0.7 (95% CI: 0.7–0.8)), the 95% limits of agreement varied from –3.0 cm to 8.0 cm. In 45 patients (21.3%), tumors were regarded as low by MRI and middle–high by endoscopy. MRI inter- and intraobserver agreements were excellent with an ICC of 0.8 (95% CI: 0.7–0.9) and 0.9 (95% CI: 0.9–1.0), respectively. The survey showed no consensus among endoscopists as to how to technically measure tumor height. Conclusion: This study showed large variability in rectal tumor height as measured by colonoscopy and MRI. Since MRI measurements showed excellent inter- and intraobserver agreement, we suggest using tumor height measurement by MRI for diagnostic purposes and treatment allocation.